Nano-Encapsulation of Brown Algal Fucoxanthin Enhances Bioavailability and Modulates Adiposity in Zebrafish (Danio rerio): Implications for Human Metabolic Syndrome - Dr. Jay Prakash Singh; Kiranjeet Kaur; Vipul Singh; Shubham Goutam; Sushant Kumar Sharma; Jitendra Kumar; Mansi Sharma; Dr. Gita Chaurasia (The Bioscan, 2026)
Background: Metabolic syndrome (MetS) represents a cluster of interconnected risk factors including obesity, hyperglycaemia, and dyslipidaemia, with increasing global prevalence. Fucoxanthin, a marine carotenoid from brown algae, exhibits anti- obesity and anti-diabetic properties but its therapeutic application is limited by poor oral bioavailability. Objective: To develop and characterize lipid-based nano capsules containing fucoxanthin (FUCO-LNCs) and evaluate their enhanced bioavailability and therapeutic efficacy in ameliorating metabolic syndrome parameters using a zebrafish model of diet-induced obesity.